A strategic management model for economic development - Diskienė, Danuta; Galinienė, Birutė; Marčinskas, Albinas (Technological and Economic Development of Economy, 2008)
In this article the authors aim to justify the structure of the strategic management model for rational economic development by evaluating the new challenges facing the national economy development. The use of the SWOT strategic planning tool is critically evaluated, and the benefits of a balanced economic expert analysis structure are substantiated. Based on the findings in this article, it is recommended that government action programmes be based on the national economic development strategy formed by independent experts and given approval by the Lithuanian Seimas (Parliament). Ūkio plėtotės strateginio valdymo modelis Santrauka. Straipsnyje, įvertinant naujus iššūkius nacionalinio ūkio plėtrai, siekiama pagrįsti racionalaus ūkio vystymo strateginio valdymo organizacinio modelio struktūrą. Kritiškai įvertinamas strateginės analizės instrumento SWOT naudojimas, pagrindžiama subalansuotos ūkio ekspertizės struktūra. Siūloma vyriausybių veiklos programose remtis nacionaline ūkio plėtros strategija, kurią formuoja nepriklausomi specialistai, įstatymais įtvirtina Lietuvos Respublikos Seimas. Reikšminiai žodžiai: strateginis ūkio vystymo valdymas, SWOT analizė, nepriklausomi ekspertai, organizacinis modelis. First published online: 21 Oct 2010